2019
DOI: 10.1002/adma.201807328
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Ion‐Conducting Switch in a Novel Single‐Ion Supramolecular Hydrogel Enabled by Photoresponsive Host–Guest Molecular Recognition

Abstract: because it can afford remote and precise control over the properties of hydrogels. [5] In recent years, a series of photo responsive hydrogel-based functional materials have been developed that show a number of emerging features, such as fluorescent, mechanical, and adhesive properties. [6][7][8][9][10] However, changing the conductivity of hydrogels by illuminationmediated ionic migration represents a promising yet challenging photoconductive property [11][12][13][14][15][16] that could be applied in many fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
133
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 36 publications
(43 reference statements)
0
133
0
1
Order By: Relevance
“…Host-guest self-assembly, typically the encapsulation behavior between small motifs and macrocycle molecules bearing cavities with a certain size, has received extensive attention in molecular recognition and stimuli-responsive systems. [1][2][3][4][5][6][7][8] Remarkably, driven by multiple non-covalent interactions such as ion-dipole, hydrophobic and H-bonding effects, macrocyclic cucurbit[n]urils (CB[n], n ¼ 5-8, typically) exhibit a robust binding strength with elaborately tailored guests to form stable binary and ternary host-guest complexes in aqueous solutions. 9,10 In the past two decades, the advancements in CB[n]based host-guest self-assembly have greatly facilitated the design of functional materials ranging from single molecules to various nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Host-guest self-assembly, typically the encapsulation behavior between small motifs and macrocycle molecules bearing cavities with a certain size, has received extensive attention in molecular recognition and stimuli-responsive systems. [1][2][3][4][5][6][7][8] Remarkably, driven by multiple non-covalent interactions such as ion-dipole, hydrophobic and H-bonding effects, macrocyclic cucurbit[n]urils (CB[n], n ¼ 5-8, typically) exhibit a robust binding strength with elaborately tailored guests to form stable binary and ternary host-guest complexes in aqueous solutions. 9,10 In the past two decades, the advancements in CB[n]based host-guest self-assembly have greatly facilitated the design of functional materials ranging from single molecules to various nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported an ion‐conducting supramolecular hydrogel based on alpha‐cyclodextrin (α‐CD), an azobenzene unit and ionic liquid which were grafted onto a gel matrix 40. The resulting gel was photoresponsive on account of the different association constants between cis ‐ and trans ‐azobenzene derivatives toward α‐CD.…”
Section: Aqueous Stimuli‐responsive Materialsmentioning
confidence: 99%
“…Polymers, representing an important platform for the combination of nanoscale chemistry and macroscopic objects, have been widely researched for potential applications in material science . The introduction of stimuli‐responsive molecular machine units into polymer systems to fabricate novel materials with advantageous properties such as self‐healability, high stretchability, and recyclability has drawn increased attention, while the introduction of responsive units may also endow these systems with controllable regulation …”
Section: Macroscale Applicationsmentioning
confidence: 99%